Expanding the clinical spectrum of intellectual disability associated with MECP2 duplication - Huyen, Le Thi Thu; Lan, Hoang Thu; Van, Nguyen Thi Khanh; Anh, Phan Ngoc; Mai, Nguyen Phuong; Anh, Luong Thi Lan (Tạp chí Nghiên cứu Y học, 2026)
Xq28 duplication or MECP2 duplication syndrome (MDS) is a rare X-linked genetic disorder characterized by intellectual disability (ID), neurodevelopmental disorders (NDDs), recurrent respiratory infections, abnormal facial features, and progressive neurological decline. Several challenges exist in the clinical identification of MDS, particularly given that most male patients inherited the chromosomal abnormality from asymptomatic or mildly symptomatic carrier mothers. The objective of our familial case series was to provide a clinical description of four males with intellectual disability across two generations in a Vietnamese family with MECP2 duplication syndrome. Chromosomal microarray analysis (CMA) was used to confirm the molecular abnormality and its segregation within the family. This familial case series illustrates typical and variable manifestations of MDS, especially changes observed from the fetal to the neonatal and adolescent period, which is essential, especially in diseases reported as progressive neurological decline, such as MECP2.